Difference between revisions of "009B Sample Midterm 1, Problem 3"
Jump to navigation
Jump to search
Line 8: | Line 8: | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | |Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int v~du.</math> | + | |'''1.''' Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int v~du.</math> |
|- | |- | ||
− | |How would you integrate <math style="vertical-align: -12px">\int x\ln x~dx?</math> | + | |'''2.''' How would you integrate <math style="vertical-align: -12px">\int x\ln x~dx?</math> |
|- | |- | ||
| | | | ||
Line 28: | Line 28: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We proceed using integration by parts. Let <math style="vertical-align: 0px">u=x^2</math> and <math style="vertical-align: 0px">dv=e^xdx</math> | + | |We proceed using integration by parts. Let <math style="vertical-align: 0px">u=x^2</math> and <math style="vertical-align: 0px">dv=e^xdx.</math> Then, <math style="vertical-align: 0px">du=2xdx</math> and <math style="vertical-align: 0px">v=e^x.</math> |
|- | |- | ||
|Therefore, we have | |Therefore, we have | ||
|- | |- | ||
− | | | + | | |
+ | ::<math style="vertical-align: -12px">\int x^2 e^x~dx=x^2e^x-\int 2xe^x~dx.</math> | ||
|} | |} | ||
Line 38: | Line 39: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we need to use integration by parts again. Let <math style="vertical-align: 0px">u=2x</math> and <math style="vertical-align: 0px">dv=e^xdx</math> | + | |Now, we need to use integration by parts again. Let <math style="vertical-align: 0px">u=2x</math> and <math style="vertical-align: 0px">dv=e^xdx.</math> Then, <math style="vertical-align: 0px">du=2dx</math> and <math style="vertical-align: 0px">v=e^x.</math> |
|- | |- | ||
|Building on the previous step, we have | |Building on the previous step, we have | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\int x^2 e^x~dx} & = & \displaystyle{x^2e^x-\bigg(2xe^x-\int 2e^x~dx\bigg)}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{x^2e^x-2xe^x+2e^x+C.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 49: | Line 55: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We proceed using integration by parts. Let <math style="vertical-align: -1px">u=\ln x</math> and <math style="vertical-align: 0px">dv=x^3dx</math> | + | |We proceed using integration by parts. Let <math style="vertical-align: -1px">u=\ln x</math> and <math style="vertical-align: 0px">dv=x^3dx.</math> Then, <math style="vertical-align: -13px">du=\frac{1}{x}dx</math> and <math style="vertical-align: -14px">v=\frac{x^4}{4}.</math> |
|- | |- | ||
|Therefore, we have | |Therefore, we have | ||
|- | |- | ||
− | | | + | | |
− | + | ::<math>\begin{array}{rcl} | |
− | + | \displaystyle{\int_{1}^{e} x^3\ln x~dx} & = & \displaystyle{\left.\ln x \bigg(\frac{x^4}{4}\bigg)\right|_{1}^{e}-\int_1^e \frac{x^3}{4}~dx }\\ | |
+ | &&\\ | ||
+ | & = & \displaystyle{\left.\ln x \bigg(\frac{x^4}{4}\bigg)-\frac{x^4}{16}\right|_{1}^{e}.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 63: | Line 72: | ||
|Now, we evaluate to get | |Now, we evaluate to get | ||
|- | |- | ||
− | | | + | | |
− | + | ::<math>\begin{array}{rcl} | |
− | + | \displaystyle{\int_{1}^{e} x^3\ln x~dx} & = & \displaystyle{\bigg((\ln e) \frac{e^4}{4}-\frac{e^4}{16}\bigg)-\bigg((\ln 1) \frac{1^4}{4}-\frac{1^4}{16}\bigg)}\\ | |
− | + | &&\\ | |
− | + | & = & \displaystyle{\frac{e^4}{4}-\frac{e^4}{16}+\frac{1}{16}}\\ | |
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{3e^4+1}{16}.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
Revision as of 13:07, 18 April 2016
Evaluate the indefinite and definite integrals.
- a)
- b)
Foundations: |
---|
1. Integration by parts tells us that |
2. How would you integrate |
|
|
|
Solution:
(a)
Step 1: |
---|
We proceed using integration by parts. Let and Then, and |
Therefore, we have |
|
Step 2: |
---|
Now, we need to use integration by parts again. Let and Then, and |
Building on the previous step, we have |
|
(b)
Step 1: |
---|
We proceed using integration by parts. Let and Then, and |
Therefore, we have |
|
Step 2: |
---|
Now, we evaluate to get |
|
Final Answer: |
---|
(a) |
(b) |